Pro WPF 4.5 in C# Windows Presentation Foundation in .NET 4.5 - MacDonald, Matthew (Apress : Imprint: Apress, 2012)
Microsoft's Windows Presentation Foundation (WPF) provides you with a development framework for building high-quality user experiences for the Windows operating system. It blends together rich content from a wide range of sources and allows you unparalleled access to the processing power of your Windows computer. Pro WPF 4.5 in C# provides a thorough, authoritative guide to how WPF really works. Packed with no-nonsense examples and practical advice you'll learn everything you need to know in order to use WPF in a professional setting. The book begins by building a firm foundation of elementary concepts, using your existing C# skills as a frame of reference, before moving on to discuss advanced concepts and demonstrate them in a hands-on way that emphasizes the time and effort savings that can be gained.